Early Intervention System: A Tool to Encourage & Support High Quality Performance - Charlotte-Mechlenburg Police (My University, 2016)
This guidebook is designed primarily to help employees of the Charlotte-Mecklenburg Police Department (CMPD) understand its Early Intervention System (EIS) processes. The CMPD EIS alerts supervisors to conduct evaluations of employees who exhibit pre-defined at-risk behaviors, and guides them in seeking avenues to address behaviors where appropriate. The guidebook also serves to inform the public about the CMPD EIS, to help create greater trust and confidence in the Department. Based on employee feedback, the 25-page guidebook uses a question-and-answer format to facilitate quick referencing of topics of interest. It was developed with funding from the COPS Office by Bill Geller, of Geller & Associates, in collaboration with CMPD Internal Affairs commander Ken Miller.